Experimental and numerical studies on the compression responses of novel mixed lattice structures. (December 2022) - Deng, Yun; Li, Bangzheng; Huang, Zhixin; Lin, Yongshui; Li, Ying
Abstract: Mechanical lattice structures have recently attracted the attention from researchers due to their lightweight and enhanced mechanical properties. Despite the dual-phase lattices have more better energy absorption capability and compression performance than the single pure lattice, limited mechanical properties still exist in the dual-phase lattices. In this work, a novel mixed structural design strategy is proposed and the specimens are fabricated by selective laser sintering. Both experimental test and numerical evaluation are conducted to validate the rationality of the proposed design strategy. Results indicate that the novel mixed lattice can achieve the higher energy absorption and lightweight in comparison with the pure and dual-phase lattice. The energy absorption efficiency could be adjusted by altering the types or sizes of basic unit cells. The proposed analytical methods can well predict the plateau stress of the mixed lattices with various geometrical dimensions. The finding of this work contributes to the designs of lattice structures with energy absorption and superior mechanical properties. Graphical Abstract: ga1